Molecular profile of pancreatic neuroendocrine neoplasms (PanNENs): Opportunities for personalized therapies. Issue 3 (3rd December 2020) - Arakelyan, Jemma; Zohrabyan, Davit; Philip, Philip A.
Abstract : Pancreatic neuroendocrine neoplasms (panNENs) are the second most common epithelial tumors of the pancreas. Despite improvements in prognostic grading and staging systems, it remains a challenge to predict the clinical behavior of panNENs and the response to specific therapies given the high degree of heterogeneity of these tumors. Most panNENs are nonfunctional and present as advanced disease. However, systemic therapies provide modest benefits. Therefore, there is a need for predictive biomarkers to develop personalized treatment and to advance new drug development. The somatostatin receptors remain the only clinically established prognostic and predictive biomarkers in panNENs. Oncogenic drivers are at a very low frequency. Commonly mutated genes in panNENs include MEN1, chromatin remodeling genes ( DAXX and ATRX ), and mammalian target of rapamycin pathway genes. In contrast, poorly differentiated neuroendocrine carcinomas (panNECs), which carry a very poor prognosis, have distinctive mutations in certain genes (eg, RB1 and p53 ). Ongoing research to integrate epigenomics will provide tremendous opportunities to improve current understanding of the clinical heterogeneity of pancreatic neuroendocrine tumors and provide invaluable insight into the biology of these tumors, new drug development, and establishing personalized therapies. Abstract : A wider application of new technologies that will go beyond simple genetic markers and would include epigenetic data will ensure that pancreatic neuroendocrine neoplasms will be managed best by molecularly tailored therapies that are currently not a standard of care.